Pedestrians Accept Shorter Distances to Light Vehicles Than Dark Ones When Crossing the Street. (May 2020) - Feldstein, Ilja T.; Peli, Eli
Does the brightness of an approaching vehicle affect a pedestrian's crossing decision? Thirty participants indicated their street-crossing intentions when facing approaching light or dark vehicles. The experiment was conducted in a real daylight environment and, additionally, in a corresponding virtual one. A real road with actual cars provides high face validity, while a virtual environment ensures the scenario's precise reproducibility and repeatability for each participant. In both settings, participants judged dark vehicles to be a more imminent threat—either closer or moving faster—when compared with light ones. Secondary results showed that participants accepted a significantly shorter time-to-contact when crossing the street in the virtual setting than on the real road.